Light sensing by opsins and fungal ecology: NOP‐1 modulates entry into sexual reproduction in response to environmental cues. Issue 1 (12th December 2017) - Wang, Zheng; Wang, Junrui; Li, Ning; Li, Jigang; Trail, Frances; Dunlap, Jay C.; Townsend, Jeffrey P.
Abstract: Understanding the genetic basis of the switch from asexual to sexual lifestyles in response to sometimes rapid environmental changes is one of the major challenges in fungal ecology. Light appears to play a critical role in the asexual–sexual switch—but fungal genomes harbour diverse light sensors. Fungal opsins are homologous to bacterial green‐light‐sensory rhodopsins, and their organismal functions in fungi have not been well understood. Three of these opsin‐like proteins were widely distributed across fungal genomes, but homologs of the Fusarium opsin‐like protein CarO were present only in plant‐associated fungi. Key amino acids, including potential retinal binding sites, functionally diverged on the phylogeny of opsins. This diversification of opsin‐like proteins could be correlated with life history‐associated differences among fungi in their expression and function during morphological development. In Neurospora crassa and related species, knockout of the opsin NOP‐1 led to a phenotype in the regulation of the asexual–sexual switch, modulating response to both light and oxygen conditions. Sexual development commenced early in ∆ nop‐1 strains cultured in unsealed plates under constant blue and white light. Furthermore, comparative transcriptomics showed that the expression of nop‐1 is light‐dependent and that the ∆ nop‐1 strain abundantly expresses genes involved in oxidative stress response, genes enriched in NAD/NADP binding sites, genes with functions in proton transmembrane movement and catalase activity, and genes involved in the homeostasis of protons. Based on these observations, we contend that light and oxidative stress regulate the switch via light‐responsive and ROS pathways in model fungus N. crassa and other fungi.